Knights of the Road: Safety, Ethics, and the Professional Truck Driver - Douglas, Matthew A. (Journal of business ethics, 2017)
Accidents involving large trucks result in significant economic and social costs. As technological solutions have improved, behavioral factors contributing to accidents have risen in importance. The purpose of this research is to investigate how norms, consequences, and personal attitudes influence safety-related ethical judgments and behavioral intentions. The Hunt–Vitell’s theory of ethical decision-making is adapted to test how these factors influence truck drivers’ decisions containing ethical content. Professional truck drivers evaluated decisions presented in two scenarios that included the situation, the decision, and the results. The research found that drivers rely heavily on evaluations of safety norms (and not reward/punishment outcomes) when forming ethical judgments and behavioral intentions. Further, drivers’ attitudes toward compliance and the effectiveness of safety regulations also influenced decision-making to an extent. Overall, evidence of a refutation of the assumption that a tradeoff exists between operational productivity and safety was discovered. Drivers in this study intended to behave in a certain manner irrespective of time or money pressures. The perceived ethical component of the decision outweighed regulatory and economic consequences under a range of parameters.